2010
DOI: 10.1242/dmm.003467
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of the metabolic syndrome

Abstract: The metabolic syndrome (MetS) is characterized by obesity concomitant with other metabolic abnormalities such as hypertriglyceridemia, reduced high-density lipoprotein levels, elevated blood pressure and raised fasting glucose levels. The precise definition of MetS, the relationships of its metabolic features, and what initiates it, are debated. However, obesity is on the rise worldwide, and its association with these metabolic symptoms increases the risk for diabetes and cardiovascular disease (among many oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
229
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(247 citation statements)
references
References 123 publications
13
229
1
4
Order By: Relevance
“…However, the observations of obesity-induced hypertension in animals are varied (32). For instance, Kennedy et al (32) recently reviewed blood pressure responses in obese mouse models such as Lep ob/ob , LepR db/db , and HFD-induced obesity; responses of blood pressure include an increase, decrease, or no change, largely depending on strain, sex, age, environment, and the method of measuring BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the observations of obesity-induced hypertension in animals are varied (32). For instance, Kennedy et al (32) recently reviewed blood pressure responses in obese mouse models such as Lep ob/ob , LepR db/db , and HFD-induced obesity; responses of blood pressure include an increase, decrease, or no change, largely depending on strain, sex, age, environment, and the method of measuring BP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observations of obesity-induced hypertension in animals are varied (32). For instance, Kennedy et al (32) recently reviewed blood pressure responses in obese mouse models such as Lep ob/ob , LepR db/db , and HFD-induced obesity; responses of blood pressure include an increase, decrease, or no change, largely depending on strain, sex, age, environment, and the method of measuring BP. In this study, we did not observe an impact from HFD on the development of hypertension in either Con-HF or Dia-HF mice; our results are similar to reported observations in 5 out of 6 nephrectomized rats fed with HFD (33) and obese ZSF1 rats (34).…”
mentioning
confidence: 99%
“…Hence, the availability of animal models that predictably reflect human obesity syndrome is important. Although the genetic models of obesity (eg, the ob/ob and db/db mice, Zucker fa/fa rats, Agouti mice, and MC4 knockout mice) have contributed significantly to our understanding of the molecular physiology of food intake and energy homeostasis [3,4] , the fact that human obesity is a complex interplay between environment (food, exercise) and genetics (multiple genes) [5,6] requires animal models that reflect this complexity.…”
Section: Introductionmentioning
confidence: 99%
“…39 Previous studies observed that the intake of cholesterol-rich food develops obesity and several cardiovascular complications in various animal models. 40,41 These high cholesterol diets induced damage to the endothelium of large arteries and heart causing hypertension and subsequently, producing atherosclerosis resulting in coronary heart disease. 42 In the present study, it is shown that there is no difference in the systolic, diastolic and mean blood pressure in the Ovx group.…”
Section: Discussionmentioning
confidence: 99%